E-Voting Application Using RSA Algorithm Method Based Prototype Android - Bagos Fitrianto Wibowo; Mohammad Iwan Wahyuddin; Endah Tri Esthi Handayani (Institute of Computer Science (IOCS), 2019)
Voting is a method of decision making. An example of the voting activity was the election of the Chair of the Communication and Information Technology Faculty (FTKI) Association at the National University which was still conducted conventionally. However, the obstacle that Occurs is that most students from each study program can not use Reviews their voting rights due to other activities. So we need a system that can Facilitate voting activities. The purpose of this research is to build an Android mobile application-based voting system to Facilitate students to be Able to vote only by using an Android smartphone connected to a particular Internet. For the data security, the RSA algorithm is used. From the system testing Carried out using the Android system version 9.0 (Pie) and the prototype method aims to produce a perfect prototype for use to the public.